Unit-Linked biztosítások modellezése az NN biztosító szemléletében - Balogh Diána (2017)
A világban nagyon fontos dolog, hogy az emberek a megtakarított pénzüket mibe és milyen módon fektetik be. Mindenki próbál hosszabb távon gondoskodni. A világban na-gyon sok problémát okoz a demográfiai eltolódás, ezért is nőhet a megtakarítások száma. Az idősebb korosztály segítséget vár az aktívan dolgozó fiatalabb társadalomtól. Azok a fiatalok, akik kezdetektől takarékoskodnak nem lesz problémájuk későbbi életükben. Erre viszont számos megoldást kínálnak a biztosító társaságok. A gyakorlatomat az NN biztosítóban töltöttem Szombathelyen. Megismerkedtem nagyon sok mindennel a cég irányításával, működésével, bele értbe a ügyfelekkel való kapcsolattartás, új szerződések kötését. A legérdekesebb feladatkörnek a befektetési egységekhez kötött életbiztosításokat tartottam, azért is választottam ez a témát. Megismerhettem az ügyfelek igényét, az NN biztosító ajánlatait, amit az ügyfeleknek kínál. Az emberek nagy része nem teheti meg, hogy a jövedelméből félretegyen, hiszen a megélhetés is nehéz. Viszont sok családban vannak felesleges kiadások, amik megszüntetése lehetőséget biztosítana a megtakarításra. A dolgozatomat úgy építettem fel, hogy mindenki számra átlátható legyen. Első fejezetben szó lesz a biztosítások kockázatairól. Bemutatom az NN Biztosítót, a biztosítások helyzetét. Az utolsó részben pedig összehasonítom más biztosítási termékkel. Abstract Nowadays, in the world and in every society it is an important question how privateindividuals can save or invest their money. The society tries to think of long-term solutions as we are talking about saving for living. Nowadays there are several popular products in the market: stocks and shares, government securities, investment bonds, or other investments which people would like to save for their flat or their retirement years and whose output could be increased with the financial help of the state. Nowadays the demographic postponement could cause a lot of problems and that is why the number of savings can increase. The older generations expect the actively working generations to support them. Those younger generations who start their savings and investments early will not have any problems in the future. The insurance companies try to offer several solutions for those people who would like to takecare of themselves and their future. During my 14-week- internship period I worked at the Szombathely branch of the NN insurance company. While working there I had the opportunity to get to know this company, its management, its control and its daily operations. My responsibilities there included making contracts with the new customers and keeping contact with the existing customers. My most interesting task was dealing with life insurances. I also had the opportunity to have a deep insight of the insurance demands, to get to know the customers’ needs, to get to know the products of the NN insurance company which were offered to the customers. I took part inpersonal meetings as well. Most of the people cannot afford to save any money as earning a living in very difficult, but there are families who can have unexpected expenditures and if they want to abolish these expenditures with the help of an insurance they can have a better future. My thesis was written in a way that those people who are not so much included in the world of insurance companies can have a better insight in these kinds of investments. In the first few chapters I am going to write about the risk and dangers of insurances. I am going to show the NN Insurance Company and its insurance products. After that I am going to write about the specific products. In the last chapter I am going to compare the NN insurance products with the products of other insurance companies.